IDENTIFICATION AND FREQUENCY OF GASTROINTESTINAL PARASITES IN CAPTIVE WILD CATS IN PERU - Aranda R., Carmen (2013)
The aim of this study was to identify gastrointestinal parasites affecting wild cats reared in captivity in four Peruvian zoos through the application of four conventional parasitological techniques (direct method, sedimentation test tube, Sheather method, Ziehl-Nielsen stain). Ten Panthera onca (4 males and 6 females), 8 Puma concolor (4 males and 4 females), 6 Leopardus pardalis (males), 3 Leopardus wiedii (1 male and 2 female) and 2 Leopardus tigrinus (males) were used. In total, 62.1% (18/29) of the individuals were positive to at least one parasite species. Panthera onca and Puma concolor were the most affected cat species (9/10 and 5/5 respectively). Among parasites, the most frequent were the cestode Spirometra mansonoides (38.9%), Toxocara cati (33.3%) and Strongyloides spp (33.3%). No significant association was found between age and sex.